Analysis of the Effects of Environmental Disclosure, Social Disclosure, and Governance Disclosure on Financial Performance in Companies Listed in the ESG Sector Leader Index of the Indonesia Stock Exchange in 2023 - Rosalia, Rosalia; Prihandini, Wiwiek (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyse the influence of Environmental, Social and Governance Disclosure on the Financial Performance of Companies Listed in the ESG Sector Leader Index of the Indonesia Stock Exchange in 2023. It is hoped that this research will provide investors with new insights into the factors that can influence financial performance as measured by Economic Value Added (EVA). In this way, investors and other financial stakeholders can consider the research findings in their decision making. The data were processed using ordinary least square (OLS) analysis, which includes a series of classical assumption tests and multiple linear regression tests to examine the results of the influence of independent variables on the dependent variable. The test results indicate that environmental disclosure, tested using four sub-variables, showed that operational carbon disclosure did not affect EVA, while product and service carbon disclosure positively affected EVA, natural resource use disclosure positively affected EVA, and emissions, effluents, and waste disclosure did not positively affect EVA. Social disclosure, tested using two sub-variables, shows that community relations disclosure and occupation health and safety disclosure do not affect EVA. Governance disclosure, tested using two sub-variables, showed that governance disclosure did not affect EVA, while business ethics disclosure did not positively affect EVA. Keywords: Environmental Social Governance (ESG), Environmental disclosure, Social disclosure, Governance disclosure, Economic Value Added